PENDAFTARAN HAK CIPTA DALAM PENEGAKAN HUKUM HAK CIPTA BERDASARKAN UU NO. 28 TAHUN 2014 TENTANG HAK CIPTA - INDRADEWI, SH.,MH, Dr. A.A SAGUNG NGURAH (Kerta Dyatmika, 2016)
ABSTRACTÂ The intellectual property rights is part of the law of property, intellectual property rights are individual rights that are intangible. existing copyright protection automatically since the creation of the birth of the creator, so registration Copyright is not a must, because without any registration of a rights reserved.Article 37 of Law Number 28 of 2014 regarding Copyright affirmed that the registration in the General Register of Copyrights shall be conducted on Yag petition filed by the creator or by the copyright holder or authorized. Creation of registration letter mentapkan early evidence of the validity of the author's copyright registration is ultimately required for the transfer of ownership for the benefit of the third party announcement for the benefit of their transition.